Vocal Artefacts: A Sonic Imagination of the Human Microphone - Phelan, Sharon (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2021)
This thesis (Vocal Artefacts) presents a body of artistic research and practice inspired by the event of the human microphone at Occupy Wall Street, Zuccotti Park, in the autumn of 2011. Vocal Artefacts conceives of the human microphone as a novel, reciprocal and embodied mode of protest — a sonic phenomenon, reflective of the cultural, social and economic shifts that lead to its emergence. The question that the research seeks to address is whether the process developed at Occupy Wall Street constitutes what Jonathan Sterne calls a ‘sonic imagination’ — an aesthetic concept towards creative and critical thinking about sound. If so, can a sonic imagination contribute towards artistic research discourse? To this end, the research situates the process of the human microphone in relation to the emerging field of sound studies. A further development of the research seeks to reflexively theorise the event of the human microphone as a site of critical creative research. The affinity between political resistance and art as artistic research was first introduced by Peter Weiss in his novel The Aesthetics of Resistance. Expanding on this connection, Hito Steyerl observes that the foundations of artistic research ‘are tied to social or revolutionary movements, or to moments of crisis and reform’. Following this paradigm, the research undertaken explores the social technology of the human microphone as an aesthetics of resistance. These two loci — sound studies and aesthetics of resistance — prompt further queries related to acts of collective voicing, political forms of listening, technologies of voice, and the relational properties of sound. Vocal Artefacts is composed of two sections: there is a written component to contextualise the artistic research, followed by an artistic (im)material enquiry. The latter incorporates chapters organised around the sonic figures of echo, parrhesia and prosopopoeia, offering a re-thinking of the relationship between voice and speech by foregrounding the voice as a sonic instrument with relational and unique properties. These sonic figures inform a series of virtual sculptures presented as a digital portfolio. The virtual sculptures explore past sites of radical potential while creating news sites through artistic means. Collectively, these art works attend to the reverberations of the human microphone through an act of sonic imagination, and attempt to reclaim art as a site of thinking and knowledge production.
APPROVED
Keywords: Artistic Research, Human Microphone, Sonic Imagination